Of one mind and of one government : the rise and fall of the Creek Nation in the early republic - Kokomoor, Kevin (New visions in Native American and indigenous studies., 2018)
"An in-depth look at the formation of Creek politics and nationalism from the 1770s through the Red Stick War, when the aftermath of the American Revolution and the beginnings of American expansionism precipitated a crisis in Creek country"--